Nanotechnology and Microtechnology in Drug Delivery Systems - Jingyao Sun; Zhaogang Yang; Lesheng Teng (SAGE Publishing, 2020)
A special issue of the journal Dose-Response entitled "Nanotechnology and Microtechnology in Drug Delivery Systems" is proposed. In pharmaceutical studies, new and existing drugs continue to be investigated for their poor specificity, solubility, therapeutic index, and immunogenicity. In order to solve these problems, drug delivery systems are essential for controlled drug release. It has been shown that the size and shape (nano- or micro-) of drug carriers can affect a drug's circulation time, distribution, and cellular uptake. Hence, it is not surprising that nanotechnology and microtechnology have been explored as powerful tools for drug delivery in past decades. The main topics will be related to the technologies including microtechnology for the sustained release of drug, nanotechnology for the targeting delivery of drugs, new polymer materials nanotechnology, nanotechnology in drugs combination application, and so on.